The natural cytokinin 2OH3MeOBAR induces cell death by a mechanism that is different from that of the "classical" cytokinin ribosides - Voller, Jiří; Béres, Tibor; Zatloukal, Marek; Kaminski, Pierre Alexandre; Niemann, Percy; Doležal, Karel; Džubák, Petr; Hajdúch, Marián; Strnad, Miroslav (Phytochemistry, 2017)
Cytokinin ribosides (N6-substituted adenosines) have demonstrated anticancer activity in various cultured cell lines, several xenografts and even a small clinical trial. Effects of kinetin riboside, N6-benzyladenosine (BAR) and N6-isopentenyladenosine on various parameters related to apoptosis have also been reported, but not directly compared with those of the highly active naturally occurring aromatic cytokinins oTR (ortho-topolin riboside) and 2OH3MeOBAR (N6-(2-hydroxy-3-methoxybenzyl)adenosine). Here we show that 2OH3MeOBAR is the most active cytokinin riboside studied to date (median, 1st quartile, 3rd quartile and range of GI50 in tests with the NCI60 cell panel: 0.19, 0.10, 0.43 and 0.02 to 15.7 μM, respectively) and it differs from other cytokinins by inducing cell death without causing pronounced ATP depletion. Analysis of NCI60 test data suggests that its activity is independent of p53 status. Further we demonstrate that its 5'-monophosphate, the dominant cancer cell metabolite, inhibits the candidate oncogene DNPH1. Synthesis, purification, HPLC-MS identification and HPLC-UV quantification of 2OH3MeOBAR metabolites are also reported.
Keywords: buněčná smrt; cytokininy; NCI60 panel; Molecular Structure; adenosin; Phytohormone; kinetin; Cytokinin; Leukemia; apoptóza; Cell Death; Glycosides; Kinetin; Cancer; glykosidy; Cytokinins; Adenosine; isopentenyladenosin; Apoptosis; molekulární struktura; Isopentenyladenosine